2013
DOI: 10.1002/eji.201243212
|View full text |Cite
|
Sign up to set email alerts
|

IFN‐β therapy modulates B‐cell and monocyte crosstalk via TLR7 in multiple sclerosis patients

Abstract: The implication of B lymphocytes in the immunopathology of multiple sclerosis (MS) is increasingly recognized. Here we investigated the response of B cells to IFN-β, a first-line therapy for relapsing-remitting MS patients, upon stimulation with TLR. IFN-β restored the frequency of TLR7-induced IgM and IgG-secreting cells in MS patients to the levels found in healthy donors, showing a specific deficiency in the TLR7 pathway. However, no difference was observed in the TLR9 response. Furthermore, in MS-derived P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 60 publications
1
22
0
Order By: Relevance
“…This structure did not activate the classical BAFF‐R transduction, but rather it was shown to drive TACI signaling 40 , 41 inducing TRAF‐mediated nuclear factor‐κB pathway and, in turn, the transcription of apoptosis‐related factors 42 . The requirement for oligomeric ligands to induce TACI signaling well fits with a model in which both TACI and BAFF are strongly upregulated as in the case of IFN‐β‐treated MS patients, in which we found that TACI expression is significantly induced in memory B cells and that BAFF is increased in both sera and peripheral blood cells as compared with therapy‐naïve patients 43 , 44 …”
Section: Discussionsupporting
confidence: 82%
“…This structure did not activate the classical BAFF‐R transduction, but rather it was shown to drive TACI signaling 40 , 41 inducing TRAF‐mediated nuclear factor‐κB pathway and, in turn, the transcription of apoptosis‐related factors 42 . The requirement for oligomeric ligands to induce TACI signaling well fits with a model in which both TACI and BAFF are strongly upregulated as in the case of IFN‐β‐treated MS patients, in which we found that TACI expression is significantly induced in memory B cells and that BAFF is increased in both sera and peripheral blood cells as compared with therapy‐naïve patients 43 , 44 …”
Section: Discussionsupporting
confidence: 82%
“…It is indicated that deficient TLR7-induced Immunoglobulin production in MS recently. The MS aggravation could be associated with impaired immune responses against infections with TLR7-recognized RNA viruses [84,85].…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Monocytes from MS patients express less TLR7 and subsequently secrete less IL-6 upon TLR7 stimulation [112]. CD14+CD16+ inflammatory monocytes are preferentially expanded in MS patients and express higher levels of activation markers compared to healthy control monocytes [113].…”
Section: Cytokine Production and Responses In The Peripherymentioning
confidence: 99%